Financial Performance Measurement with the Use of Financial Ratios: Case of Mongolian Companies - Batchimeg, Bayaraa (International Journal of Engineering and Management Sciences, 2017)
The aim of this paper is to examine the efficiency of Mongolian 100 public companies listed on Mongolian Stock Exchange (MSE) which are divided into 6 major sectors. This study conducts the performance of companies in terms of profitability by using three different output variables i.e., revenue, pretax profit and ROA (Return on Assets). In the beginning of this research, nine variables which are connected with profitability are chosen as output variables, while 24 variables expressing growth, financial structure, solvency, and turnover together with some fundamental financial data are chosen as input variables. 10 variables out of 24 input variables, which determine the financial structure, solvency, and profitability, are chosen as input variables based on the calculation of stepwise regression analysis. Stepwise regression, multi co-linearity analysis are made by SPSS and DEA (Data envelopment analysis) is evaluated by benchmarking package in R excel statistical program covering the period of 2012-2015. This paper uses the input-oriented version of DEA based on financial ratios and some crucial components of a financial statement. The results of DEA show that food and grocery sector was the most efficient, and mining sector was at the second place by its efficiency, while agriculture and service sector were the worse than other sectors.